CORRELATION OF WORKER WELFARE AND INDUSTRIAL RELATIONS - Sudja’i Sudja’i; Rahayu Mardikaningsih (Transpublika Publisher, 2021)
The smooth running of business in activities in the workplace occurs when there is a harmonious relationship between employers and workers based on working relationships in an industrial environment. Workers should feel well-being as part of the membership of a business enterprise. This study aims to determine the correlation between worker welfare and industrial relations. Observations were made in a company with a workforce of more than 1000 people in East Java Province. The number of samples taken was 100 people with purposive sampling technique. The collected data is then processed through the SPSS program with statistical correlation techniques. The results obtained are that there is a significant correlation of worker welfare and industrial relations. The form of correlation is positive or unidirectional and quite strong. The better and the welfare felt by the workers, the better and harmonious industrial relations will be created on both sides.